Influence of Temperature and Blending Ratio on Product Yield for Co-gasification of Torrefied Palm Kernel Shell (TPKS) and Low-Density Polyethylene (LDPE) - Ibrahim, Nur Rahimah; Ahmad, Razi; Mohd Ishak, Mohd Azlan; Siripatana, Chairat (International Journal of Integrated Engineering, 2024)
This study investigated the product yields produced from the co-gasification of torrefied palm kernel shell (TPKS) and low-density polyethylene (LDPE). Prior co-gasification, PKS was undergo pre-treatment process at different temperature. The optimum parameter for torrefaction was found at 250 oC for 60 min reaction time with 4.89 wt.% moisture content and 10.48 wt.% fixed carbon. Thus, the result indicated that TPKS a suitable fuel feedstock for further thermal conversion. Then, TPKS and LDPE were gasified at different temperature and blending ratio for 60 min reaction time. The results showed that, temperature plays an important role in co-gasification. Higher gasification temperature increases the carbon conversion which improves gasification rate. By varying temperature from 600 to 1000 oC, the gas yield increased considerably from 25.88 to 45.94 wt.%, whilst tar yield decreased sharply from 49.61 to 35.03 wt.%. However, as temperature increased from 800 to 1000 oC, tar yield increased from 26.58 to 35.03 wt.%. Meanwhile, char yield decreased from 24.50 wt.% to 19.02 wt.% over the temperature range of 600 to 1000 oC. For the effect of blending ratio, through blending of TPKS and LDPE, the gas and char yield increase, while tar decrease with increase torrefied TPKS ratio. Furthermore, it was observed that the product yields obtained from the co-gasification of TPKS and LDPE at 50:50 blending ratios produce the highest gas yield with low char and tar yield than another blending ratio. Therefore, based on the effect of temperature and blending ratio on product yield shows that the optimum parameter to produce maximum gas yield with minimum tar and char yield are at 50:50 (TPKS:LDPE) blending ratio at 800oC for 60 minutes reaction time. The gas analysis exhibited the H2 composition was increased drastically with increase reaction time for TPKS:LDPE compared than UnPKS:LDPE. The high production of H2 is in accordance with the high quantity of carbon content in TPKS compared to UnPKS. As a result, the pretreatment of PKS enhanced the H2 production during co-gasification of TPKS and LDPE.